2008
DOI: 10.1111/j.1465-3435.2007.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Students' Preferences and Needs in Portuguese Higher Education

Abstract: In Portugal, there is a diversified higher education system comprising some 160 institutions: universities, polytechnics and isolated schools, public or private, with a total enrolment of some 350,000 students. This article presents the analysis of the results of questionnaires which were completed in 2004 by students entering higher education for the first time so as to understand their perceived needs and aspirations and how they chose their institution/study programme. In the last few years, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 8 publications
2
37
0
4
Order By: Relevance
“…The testimonials from the current students enrolled for a particular program also influence the students' choice. Furthermore, Tavares et al (2008) claimed that 'vocation' or specialisation was a stronger reason for program choice than employment prospects.…”
Section: Program Structurementioning
confidence: 99%
“…The testimonials from the current students enrolled for a particular program also influence the students' choice. Furthermore, Tavares et al (2008) claimed that 'vocation' or specialisation was a stronger reason for program choice than employment prospects.…”
Section: Program Structurementioning
confidence: 99%
“…Wagner and Fard (2009), and Leister and Menzel (1976) found that geographical position and the size of the university are important factors in university selection. Tavares et al (2008) revealed that some institutional characteristics like the quality of education, academic reputation, infrastructure, facilities like a library and computer labs, the location of the university, the quality of the program and scientific research, the support given by the administration, extra-curricular activities (sports activities, free-time activities, canteens etc.) and exchange programs with the universities abroad are the important criteria students use to select a university.…”
Section: Yapılandırılmışmentioning
confidence: 99%
“…Parity of participation (Fraser&Honneth, 2003) provides a workable definition of justice, while vulnerability (Fineman, 2008) and capabilities (Sen, 1999) focus on more institutional and individual aspects of the parity of participation norm that also privilege a comparative approach. Nancy Fraser is a feminist philosopher concerned with matters of justice regarding gender and class.…”
Section: Parity Of Participation Vulnerability and Capabilities: A Tmentioning
confidence: 99%
“…While it is useful to delimitate vulnerability as an intrinsic human feature, such conceptual framework would not be complete without introducing the capability approach as a positive counterpart of vulnepraktyka t e o r e t y c z n a rability. The capability approach is a normative framework for evaluating the quality of life developed by (Sen 1999) and further used on the United Nations' Index of Human Development. According to (Sen 1999), capabilities are the set of real opportunities an individual has to choose from in order to achieve a life she has reason to value.…”
mentioning
confidence: 99%
See 1 more Smart Citation